Addressing the Reproducibility of Photocatalytic Carbon Dioxide Reduction. Issue 6 (12th December 2019) - Marx, Maximilian; Mele, Andrea; Spannenberg, Anke; Steinlechner, Christoph; Junge, Henrik; Schollhammer, Philippe; Beller, Matthias
Abstract: Reproducibility of photocatalytic reactions, especially when conducted on small scale for improved turnover numbers with in situ formed catalysts can prove challenging. Herein, we showcase the problematic reproducibility on the example of attractive photocatalytic CO2 reduction utilizing [FeFe] hydrogenase mimics. These Fe complexes, well‐known for their application in proton reduction reactions, were combined with a heteroleptic Cu photosensitizer and produced CO/H2 /HCO2 H mixtures of variable constitution. However, the reactions indicated a poor reproducibility, even when conducted with well‐defined complexes. Based on our experience, we make suggestions for scientists working in the field of photocatalysis on how to address and report the reproducibility of novel photocatalytic reaction protocols. In addition, we would like to highlight the importance of studying reproducibility of novel reaction protocols, especially in the fields of photocatalytic water splitting and CO2 reduction, where TONs are widely used as the comparable measure for catalytic activity. Abstract : Photocatalysis : Reproducibility for photocatalytic CO2 reduction has been evaluated on the example of [FeFe] hydrogenase mimics in combination with a heteroleptic Cu photosensitizer. Based on these results, we highlight the importance of testing reproducibility for new photocatalytic reaction protocols. Furthermore, we provide suggestions on how to ensure reproducibility of those transformations.